Безпекова екологічна політика в контексті реалізації цілей сталого розвитку - Дзюндзюк, Вячеслав Борисович; Дзюндзюк, Борис Вячеславович (Національний технічний університет "Харківський політехнічний інститут", 2023)
У статті розглянуто сучасний стан формування системи державного регулювання та проблемні питання забезпечення безпекової екологічної політики в контексті реалізації цілей сталого розвитку в Україні в нових умовах. Обґрунтовано теоретико-методологічні положення та розроблено концептуальні засади вдосконалення державного регулювання природоохоронної системи. Безпекова екологічна політика виступає важливим компонентом державної політики у сфері національної безпеки. У контексті реалізації цілей сталого розвитку в Україні необхідно вдосконалити систему державного регулювання природоохоронної системи. Екологічні проблеми можуть призвести до дестабілізації суспільства, порушення нормального функціонування економіки та погіршення якості життя населення. Тому важливо розробити та реалізовувати ефективні заходи щодо забезпечення екологічної безпеки. Пропоновані авторами статті заходи є актуальними та можуть сприяти вдосконаленню системи державного регулювання природоохоронної системи в Україні.

The article examines the current state of the formation of the state regulatory system and the problematic issues of ensuring a safe environmental policy in the context of the implementation of the goals of sustainable development in Ukraine in new conditions. The theoretical and methodological provisions were substantiated and the conceptual principles of improving the state regulation of the nature protection system were developed. Environmental safety policy is an important component of state policy in the field of national security. In the context of the implementation of the goals of sustainable development in Ukraine, it is necessary to improve the system of state regulation of the nature protection system. Environmental problems can lead to destabilization of society, disruption of the normal functioning of the economy and deterioration of the quality of life of the population. Therefore, it is important to develop and implement effective measures to ensure environmental safety. The measures proposed by the authors of the article are relevant and can contribute to the improvement of the system of state regulation of the nature protection system in Ukraine.
Safe environmental policy in context implementation of sustainable development goals
Keywords: державна екологічна політика; державна політика у сфері національної безпеки; забезпечення екологічної безпеки; state environmental policy; state policy in the field of national security; ensuring environmental security